Controversy in the Biography of Jonas Noreika-General Vėtra - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2016)
The article focuses on the exploration of the biography of the famous Lithuanian resistance activist Jonas Noreika-General Vėtra (8 October 1910 to 26 February 1947). It raises two questions related to the specific nature of his activities during the Nazi occupation and his relationship with the Holocaust. In order to answer these questions his life in the pre-resistance period, the period of resistance fight, and his relationship with the Holocaust are explored. The pre-resistance period in Noreika’s biography covers the period from 8 October 1910 to 15 June 1940. It is described as the period of the formation of personal qualities of Noreika. The role of his family, elementary school, Šiauliai Boys Gymnasium, Military School, Vytautas Magnus University, Lithuanian Army, and other factors is revealed. Noreika is described as a person with the intrinsic qualities of a representative of the modern Lithuanian nation. He demonstrated national self-awareness and awareness as a member of the ethno-political community. Information about his qualities as an army officer is provided. The period of resistance fight in Noreika’s biography covers the period from 15 June 1940 to his death on 26 February 1947. At first, a general overview of this period in his life, which is subdivided into seven subperiods, is provided. Subsequently, the second and third subperiods in his resistance activities, when he was the commander of the Lithuanian Activist Front of Telšiai County and the governor of Šiauliai County Municipality, are explored These two periods are in focus due to the fact that there are some claims in historical literature that Noreika could have been linked to the Holocaust in this period. It is alleged that the occupation and annexation of Lithuania in summer 1940 carried out by the Soviet Union, the imposed Bolshevik concept of the state, Communist ideology, and destruction of the public order formed in Lithuania on 16 February 1918 were causes of his traumatic experience and the motivation behind his resistance activities. The stimulus for his activities was his desire that Lithuania would be an independent state again, that the country and its citizens would be protected against the disastrous consequences of the Soviet regime; he was also stimulated by the harm he suffered during the Soviet period, his wish to reverse his worsening situation, and his love of the country. During the period of resistance fight in Noreika’s life he nurtured a desire to resist against the aggressors which occupied Lithuania. In addition, in the first, second, third and sixth subperiods, he was practically engaged in anti-Soviet resistance activities. In the third subperiod of his life, in addition to anti-Soviet resistance, he engaged into anti-Nazi resistance. He planned two forms of anti-Soviet resistance fight – underground organisational actions and armed resistance actions – in the first subperiod (from 5 June 1940 to 28 June 1941) and sixth subperiod (from 27 November 1945 or his return to Vilnius to his arrest on 16 March 1946). In both subperiods the aim of the underground organisational actions was to prepare for the uprising, which should have taken place at the outbreak of the war between the foreign state and the occupying state. During the first subperiod he became involved in resistance actions leading a group of rebels of Plungė Rural Area of Telšiai County during the June 1941 Uprising in Lithuania. During the sixth subperiod, Noreika did not participate in resistance fight as the war did not break out, furthermore he and his fellow fighters were in detention. Meanwhile during the second subperiod (28 June 1941–2 August 1941 when he served as the commander of the Lithuanian Activist Front of Plungė Rural Area of Telšiai County) and third subperiod (3 August 1941–23 February 1943 when he held the position of the governor of Šiauliai County Municipality) in his life under the German occupation of the country, he engaged into anti-Soviet activities through the use of publicity and underground organisational actions. During the second subperiod, acting as the commander of the Lithuanian Activist Front of Telšiai County in the uprising, Noreika publicly demonstrated his wish to contribute to the reestablishment of the independent state of Lithuania declared on 23 June 1941. In the third subperiod, publicity as the form of resistance was used for anti-Soviet propaganda and the actual underground organisational actions involved collection of weapons to fight against the Soviets. In the same third subperiod, Noreika used underground organisational actions, partial non-cooperation and disobedience as forms of anti-Nazi resistance. Partial non-cooperation and disobedience reflected in his attempts to protect the population against the negative and disastrous consequences of the policy pursued by the Nazi occupation authorities in the country. Noreika did not resort to armed resistance as his anti-Nazi resistance activity, because this would have meant support for the Soviet Union and the threat of the new occupation and annexation by the USSR was still imminent. Finally, a period in Noreika’s life when he held the position of the governor of Šiauliai County Municipality is reviewed by exploring his links to the Holocaust. This is performed by using the paradigms of the Holocaust proposed by researcher Raul Hilberg. The arguments are provided why Noreika cannot be considered as one of those who created the legal racists concept of the Jew. Based on historical sources and history research, versions provided by the Lithuanian emigrant, Aleksandras Pakalniškis, and the former detainee of Šiauliai Ghetto, Leiba Lipsic, that in summer and autumn 1941 Noreika participated in mass extermination campaigns of Jews in Plungė Rural Area of Telšiai County and Šiauliai County, are contradicted. The said persons allege that Noreika’s activities when he held the position of the governor of Šiauliai County Municipality involved expropriation of Jewish property and collection of Jews. On 22 August 1941, Noreika passed an order from Walter Gewecke, commissioner of Šiauliai Military District, to governors of rural areas and burgomasters of minor towns, regarding the relocation of the Jews of the county to Žagarė Ghetto. The order was enforced and carried out by the Lithuanian police forces, but not by the municipal officials of the county under Noreika’s control. The Lithuanian municipal officials (Noreika was among them) administered the issues of taking over and disposing of the Jewish property. The opinion that Noreika established Žagarė Ghetto is incorrect. It was established in the second half of July 1941 when Noreika was the commander of the Lithuanian Activist Front of Plungė Rural Area of Telšiai County, whereas Ignas Urbaitis held the position of the governor of Šiauliai County.